1967
DOI: 10.2136/sssaj1967.03615995003100060010x
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Boron by Layer Silicates, Sesquioxides, and Soil Materials: I. Layer Silicates

Abstract: The characteristics of boron retention by layer silicates were studied. Boron retention was determined by a procedure developed for use with solution concentrations ranging from zero up to several hundred parts per million B, which consisted of treatment of the adsorbent with B solutions, washing with methanol to remove excess B, and extracting the retained B with 0.01N NaCl (pH 3).Vermiculite, kaolinite, montmorillonite, and hydrobiotite all exhibited a pH‐dependent affinity for B with maxima in the alkaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1
11

Year Published

1977
1977
2012
2012

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 0 publications
5
33
1
11
Order By: Relevance
“…Frederickson & Reynolds (1959) proposed that most of the B in the clay mineral fraction of sedimentary rocks is contained in the illite fraction. Sims & Bingham (1967, 1968a, 1968b found that B adsorption was greater for iron (Fe) and Al coated kaolinite or montmorillonite than for uncoated clays. It was concluded that hydroxyl of Fe and Al compounds present in the layer as silicates or as impurities dominate over clay mineral species per se in determining B adsorption characteristics.…”
Section: Soil Texture and Clay Mineralsmentioning
confidence: 99%
“…Frederickson & Reynolds (1959) proposed that most of the B in the clay mineral fraction of sedimentary rocks is contained in the illite fraction. Sims & Bingham (1967, 1968a, 1968b found that B adsorption was greater for iron (Fe) and Al coated kaolinite or montmorillonite than for uncoated clays. It was concluded that hydroxyl of Fe and Al compounds present in the layer as silicates or as impurities dominate over clay mineral species per se in determining B adsorption characteristics.…”
Section: Soil Texture and Clay Mineralsmentioning
confidence: 99%
“…In soils, B undergoes adsorption and these reactions control the amount of B available in soil solution for uptake by plants (Goldberg 1997). In adsorption reactions, the borate anion (B(OH) 4 − ) replaces surface hydroxyl groups on iron (Fe) and aluminium (Al) oxides, clay minerals, sesquioxides and organic matter (Martens 1968, Sims and Bingham 1967, 1968a, 1968b. The level of adsorption of B and consequently, the amount of plant-available B in soil solution is controlled by a soil's specific physical and chemical properties, including pH, soil texture, clay mineralogy, and organic matter content (Goldberg 1997).…”
Section: B Chemistry and Usesmentioning
confidence: 99%
“…A disponibilidade de B nos solos para as plantas é afetada, principalmente, pelos fatores: pH, teor de matéria orgânica, tipo de argila, textura, compostos de Fe e Al (Kubota et al, 1948;Parks & White, 1952;Gupta, 1968;Sims & Bingham, 1967Choi & Chen, 1979), dentre outros. Por isso, em alguns casos, a inclusão de alguns atributos dos solos na análise de regressão pode ser importante na predição da disponibilidade de B dos solos (Gestring & Soltanpour,1984).…”
Section: Introductionunclassified